2012
DOI: 10.3390/molecules171011849
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Synthesis of Betulonic Acid Using Selective Oxidation of Betulin on Aluminium Solid Support

Abstract: The room temperature oxidation of betulin by Cr(VI) compounds in aqueous acetone on solid supports such as alumina, zeolites and silica gel has been studied. The oxidation on alumina support leaded to a single product—betulonic acid—in quantitative yield. One hundred percent selective oxidation during 30 min of betulin up to betulonic aldehyde was determined when silica gel support was used. The oxidation of betulin using zeolites as a support gives a mixture of betulonic acid and aldehyde in a 2:1 ratio. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Betulonic acid was considered for a long time only as a precursor of betulinic acid obtained in syntheses [21], however, recent studies have shown a number of valu able characteristics of betulonic acid such as antiviral, anticancer, antimicrobial, hepatoprotective, and immunostimulatory properties [22][23][24][25][26][27]. Investigation of the influence of derivatives of betulonic acid in com bination with rimantadine on influenza virus has shown the possibility of reducing both side effects and dose of the drug due to the use of this combination [28].…”
Section: Introductionmentioning
confidence: 99%
“…Betulonic acid was considered for a long time only as a precursor of betulinic acid obtained in syntheses [21], however, recent studies have shown a number of valu able characteristics of betulonic acid such as antiviral, anticancer, antimicrobial, hepatoprotective, and immunostimulatory properties [22][23][24][25][26][27]. Investigation of the influence of derivatives of betulonic acid in com bination with rimantadine on influenza virus has shown the possibility of reducing both side effects and dose of the drug due to the use of this combination [28].…”
Section: Introductionmentioning
confidence: 99%
“…Betulin-3,28-diacetate (BDA) and betulonic acid (BA) were synthesized according to the methods described in [14,15], respectively. Spectral data were the following:…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, various attempts have been made to obtain betulinic acid, using betulin as a starting point. In the study of Melnikova and co-workers [61], the most intense catalytic activity was noticed for aluminum salts, which also have a selective activity. The reaction proceeds via the intermediate betulonic acid, purified by recrystallization.…”
Section: Obtainment Of Lupane-skeleton Triterpenes With Efficacy In Smentioning
confidence: 96%
“…The reaction proceeds via the intermediate betulonic acid, purified by recrystallization. Betulonic acid is reduced with NaBH 4 (THF or isopropanol) at room temperature to obtain a mixture of 3α-betulinic acid and betulinic acid-3β [61].…”
Section: Obtainment Of Lupane-skeleton Triterpenes With Efficacy In Smentioning
confidence: 99%